Functional threshold power: Relationship with respiratory compensation point and effects of various warm-up protocols - Barranco-Gil, D.; Gil-Cabrera, J.; Valenzuela, P. L.; Alejo, L. B.; Montalvo-Pérez, A.; Talavera, E.; Moral-González, S.; Lucia, A. (International Journal of Sports Physiology and Performance, 2020)
Purpose: The functional threshold power (FTP), which demarcates the transition from steady state to non-steady-state oxidative metabolism, is usually determined with a 20-minute cycling time trial that follows a standard ~45-minute warm-up. This study aimed to determine if the standard warm-up inherent to FTP determination is actually necessary and how its modification or removal affects the relationship between FTP and the respiratory compensation point (RCP). Methods: A total of 15 male cyclists (age 35 [9] y, maximum oxygen uptake 66.4 [6.8] mL/kg·min) participated in this randomized, crossover study. Participants performed a ramp test for determination of RCP and maximum oxygen uptake. During subsequent visits, they performed a 20-minute time trial preceded by the "standard" warm-up that is typically performed before an FTP test (S-WU), a 10-minute warm-up at the power output (PO) corresponding to 60% of maximum oxygen uptake (60%-WU), or no warm-up (No-WU). FTP was computed as 95% of the mean PO attained during the time trial. Results: Although the FTP was correlated with the RCP independently of the warm-up (r=.89, .93, and .86 for No-WU, 60%-WU, and S-WU, respectively; all Ps<.001), the PO at RCP was higher than the FTP in all cases (bias±95% limits of agreement=57 [24], 60 [23], and 57 [32] W for No-WU, 60%-WU, and S-WU, respectively; all Ps<.001 and effect size > 1.70). Conclusions: The FTP is highly correlated with the RCP but corresponds to a significantly lower PO, being these results independent of the warm-up performed (or even with no warm-up).